Theoretical and methodological basis of the use of digital technologies in the formation of environmental competence of applicants for education - Mironets, Liudmyla; Tolochko, Svitlana (ScienceRise: Pedagogical Education, 2023)
The article contains the results of scientific research on the theoretical and methodological foundations of the use of digital technologies in the formation of environmental competence of applicants for education. The purpose of the study is to conduct an analysis of theoretical and methodological foundations of the use of digital technologies in the formation of environmental competence of applicants for education in order to create methodological recommendations for teachers to carry out distance and blended learning. Peculiarities of the use of digital technologies in the formation of environmental competence of applicants for education are analyzed (intensification of learning due to the use of attractive and rapidly changing forms of information presentation, promotion of learning individualization; interrelation of portions of information and tests; strict logical sequence, structural and logical schemes; doing tests and solving tasks; having several attempts, learning the material anew or reperforming tasks). Characteristics of online platforms for use in the process of forming environmental competence of applicants for education according to their features, advantages and disadvantages, including Google Apps Education Edition, Google Classroom, Google Meets, Teams, Moodle, Zoom, Classtools, LearningApps, Edmodo, etc., were studied. A method of using mobile applications with ecological content in the formation of environmental competence of applicants for education has been developed through the determination of ways of their integration into educational and cognitive activities, locations (autonomous work in the educational building or remotely); frequency of their application (a prepared educational course, a project with usage of mobile technologies or a one-time integration into an educational session in the process of exploring a certain topic); creation and use of existing mobile applications; use of personal mobile devices or devices of educational institutions.